GlideScope Cobalt Videolaryngoscope: Mirrors and Illusions. (February 2015) - Fiadjoe, John E.; Isserman, Rebecca S.; Gurnaney, Harshad; Kovatsis, Pete G.
Abstract : Supplemental Digital Content is available in the text.